(3GdCUhd GdELJeGYjI ddJfejI GdEbJUGOjIs - (3eMeO fHjd(B, (3LGeYs ((3GdEScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI ddfTQ(B,s)
(3GdYhdeI hYde GdELJeGY GdEbJUGOj(B- (3eaghe hfTCI hQhGO Yde GdELJeGY GdEbJUGOj(B- (3GdWHjYI GdELJeGYjI ddfXe hGdhMOGJ GdEbJUGOjI(B- (3GMjGA GdghjI GdELJeGYjI dYde GdEbJUGO GdeYGUQ(B- (3eaghe hbjGS GdGhVGY GdeDSSjI aj eUQ hHYV GdOhd GdYGde(B- (3EOGQI GdMcheI hGdGef Gdbhej(B- (3GLJeGYjGJ GdeTQhYGJ GdUZjQI hOYegG GdEbJUGOj(B- (3GLJeGYjGJ GdMjGRI GdeRQYjI HGdBQGVj GdLOjOIs
(3GdeQGLY U(B509s
Keywords: (3GdELJeGY, Yde s; (3GdJfejI GdEbJUGOjIs; (3Yde GdELJeGY GdEbJUGOjs